2021
DOI: 10.1140/epje/s10189-021-00052-7
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell motile behaviour of $${Trypanosoma\, brucei}$$ in thin-layered fluid collectives

Abstract: We describe a system for the analysis of an important unicellular eukaryotic flagellate in a confining and crowded environment. The parasite Trypanosoma brucei is arguably one of the most versatile microswimmers known. It has unique properties as a single microswimmer and shows remarkable adaptations (not only in motility, but prominently so), to its environment during a complex developmental cycle involving two different hosts. Specific life cycle stages show fascinating collective behaviour, as millions of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…Movement of pedestrians or insect groups such as ants is often restricted by fences or walls that limit a channel [22]. Collective behaviour of unicellular organisms is typically studied in quasi two-dimensional disklike liquid droplets [23] or in microfluidic devices with channels as well as chambers of different shapes including disks and boxes [24]. Our work provides a further step towards the application of the Vicsek model to study such systems.…”
Section: Discussionmentioning
confidence: 99%
“…Movement of pedestrians or insect groups such as ants is often restricted by fences or walls that limit a channel [22]. Collective behaviour of unicellular organisms is typically studied in quasi two-dimensional disklike liquid droplets [23] or in microfluidic devices with channels as well as chambers of different shapes including disks and boxes [24]. Our work provides a further step towards the application of the Vicsek model to study such systems.…”
Section: Discussionmentioning
confidence: 99%
“…Application of our methods to in vitro trypanosome colonies reveal that simple growth dynamics as represented by the Eden model are not sufficient to accurately capture social motility dynamics. However, in combination with data from single cells [9], our colony-scale quantification builds a solid basis for developing more intricate models, that could incorporate factors such as cell division, characteristics of the microswimmer motion and the properties of the colony boundaries. Hence, we are one step further in understanding the mechanisms of collective trypanosome motion in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…These results highlighted the importance of as yet unclear physical parameters underlying the phenomena of SoMo. [9].…”
Section: Introductionmentioning
confidence: 99%
“…This is independent of the question whether trypanosomes display true swarming, defined as directional motility of groups of cells, mainly observed in prokaryotic systems 6 . A careful analysis of the SoMo process on plates showed that single fluorescently labeled trypanosomes in projections did not move directionally and single cell motility did not correlate with movement of the projections 70 . In dissected tsetse fly tissues, collective motion of trypanosomes as synchronized swarms with coordinated flagellar beat were observed ex vivo 11 .…”
Section: Discussionmentioning
confidence: 99%